Military Culture: Masculine Norms, Perceived Personal Control, Autonomous Motivation, and Coping Differences Between Injured Male Military Personnel and Civilian Sportsmen. (3rd April 2019) - Paskell, Rachel; Gauntlett-Gilbert, Jeremy; Wilkinson-Tough, Megan
Abstract: Engagement in rehabilitation is critical to enhanced outcomes from musculoskeletal injuries (MIs) and has been found to be related to some psychosocial factors. This study tested whether military culture, defined by greater adherence to masculine norms; higher levels of perceived personal control and autonomous motivation; lower levels of emotion-focused coping strategies; and a greater use of problem-focused coping strategies, resulted in better engagement in rehabilitation following MI. These hypothesized cultural differences were measured by administration of validated self-report questionnaires (Brief Illness Perception Questionnaire; Conformity to Masculine Norms Inventory; Treatment Self-Regulation Questionnaire; and the Brief COPE). A between-groups quasi-experimental design compared self-report variables and physiotherapist engagement ratings for 16 male military personnel and 22 committed sportsmen. All participants had sustained musculoskeletal injuries within the past 6 months, for which they were having physiotherapy. No evidence was found for the presence of a hypothesized military culture defined by greater adherence to masculine norms, higher levels of perceived personal control and autonomous motivation, and greater use of problem-focused coping strategies. Clinical and research implications are discussed with recommendations for future work to build upon this study.